2011
DOI: 10.3758/s13415-011-0075-5
|View full text |Cite
|
Sign up to set email alerts
|

Brain oscillatory activity associated with task switching and feedback processing

Abstract: In this study, we sought to dissociate eventrelated potentials (ERPs) and the oscillatory activity associated with signals indicating feedback about performance (outcome-based behavioral adjustment) and the signals indicating the need to change or maintain a task set (rule-based behavioral adjustment). With this purpose in mind, we noninvasively recorded electroencephalographic signals, using a modified version of the Wisconsin card sorting task, in which feedback processing and task switching could be studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
100
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(124 citation statements)
references
References 105 publications
(146 reference statements)
16
100
1
1
Order By: Relevance
“…Previous research had suggested that beta-gamma activity is a possible neural marker of reward associated with monetary gains (Marco-Pallarés et al, 2008;Marco-Pallarés et al, 2009) and positive feedback (Cohen et al, 2007;Cunillera et al, 2012;Haji Hosseini et al, 2012). Animal studies have observed increases of beta activity in the striatum after reward delivery (Courtemanche, Fuji, & Graybiel, 2003).…”
Section: Consummatory Responses To Monetary Rewards In Anhedoniamentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research had suggested that beta-gamma activity is a possible neural marker of reward associated with monetary gains (Marco-Pallarés et al, 2008;Marco-Pallarés et al, 2009) and positive feedback (Cohen et al, 2007;Cunillera et al, 2012;Haji Hosseini et al, 2012). Animal studies have observed increases of beta activity in the striatum after reward delivery (Courtemanche, Fuji, & Graybiel, 2003).…”
Section: Consummatory Responses To Monetary Rewards In Anhedoniamentioning
confidence: 99%
“…In this sense, it has been proposed that medial frontal theta activity represents the broad coordination of several brain regions implicated in action monitoring and control processes (Cavanagh et al, 2010). Accordingly, theta power increases seem to be relevant for task switching (Cunillera et al, 2012), for improving learning (van de Vijver et al, 2011), and for future behavioral adjustments (Cavanagh, Cohen, & Allen, 2009;Cavanagh et al, 2010;Womelsdorf et al, 2010).…”
Section: Consummatory Responses To Monetary Rewards In Anhedoniamentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with findings from other paradigms that rely primarily on reactive control processes. In a cued-Wisconsin Card Sorting task, cues associated with a rule switch led to sustained theta band activity across frontal and parietal sites, as well as a decrease in centro-parietal alpha band power (Cunillera et al, 2012). However, using a cued-trial paradigm, Mansfield et al, (2012) found differences in low-mid frequency oscillations between switch and repeat cues, relative to a non-informative cue baseline, over right frontal and bilateral parietal sites in time windows corresponding the early switchpositivity and pre-target negativity, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In turn, the P3 is a slow centro-parietal component associated with the updating of relevant (i.e., motivationally salient) external information, formation of new decisions, and consequent changes in behavior according to task contingencies (Barcelo, Escera, Corral, & Perianez, 2006;Chase, Swainson, Durham, Benham, & Cools, 2011;Fischer & Ullsperger, 2013). For instance, the P3 component is usually enhanced after stimuli indicating the request to implement a new rule change (e.g., in the Wisconsin Card Sorting Task and the Reversal Learning Task; Chase et al, 2011;Cunillera et al, 2012). Centro-parietal EEG activity indexed by the P3-like components may possibly echo brain computations, reflecting the accumulation of internal evidences that an error (or erratic behavioral trend) has occurred (Steinhauser & Yeung, 2010) and deliberate changes in behavior may be required.…”
mentioning
confidence: 99%